Presentation and Management of Pediatric Orbital Cellulitis - Sergio Fanella; Alex Singer; Joanne Embree (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Orbital cellulitis is a serious, vision-threatening infection.